2004
DOI: 10.1534/genetics.166.1.565
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Genetic Conflict on Genomic Imprinting and Modification of Expression at a Sex-Linked Locus

Abstract: We examine how genomic imprinting may have evolved at an X-linked locus, using six diallelic models of selection in which one allele is imprintable and the other is not. Selection pressures are generated by genetic conflict between mothers and their offspring. The various models describe cases of maternal and paternal inactivation, in which females may be monogamous or bigamous. When inactivation is maternal, we examine the situations in which only female offspring exhibit imprinting as well as when both sexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
1
19
1
Order By: Relevance
“…Previous models concerned with the evolution of imprinting from standard expression (Spencer et al 1998(Spencer et al , 2004 have found a similar result, but these latter models all involved both imprintable and unimprintable alleles. Pearce and Spencer (1992) investigated the effect of imprinting on standard models of viability selection.…”
Section: Discussionmentioning
confidence: 69%
“…Previous models concerned with the evolution of imprinting from standard expression (Spencer et al 1998(Spencer et al , 2004 have found a similar result, but these latter models all involved both imprintable and unimprintable alleles. Pearce and Spencer (1992) investigated the effect of imprinting on standard models of viability selection.…”
Section: Discussionmentioning
confidence: 69%
“…Consequently, X-linked traits with different male and female optima should be selected to be imprinted to take advantage of this mechanism for differential male/female expression and, moreover, X-linked growth enhancers should be maternally active in most eutherians as males are general larger than females. This prediction, the opposite of that of the genetic conflict model (even as applied to X-chromosome inactivation; see Spencer et al, 2004), explains the monosomic mouse data (Iwasa and Pomiankowski, 1999).…”
Section: X-linked Sex-specific Selectionmentioning
confidence: 81%
“…Benefits of 'resemblance' that have been proposed to explain the evolution of parent-specific expression include: paternally-inherited antigens of the placenta are silenced to avoid mismatch between maternal and fetal antigens (Elinson, 1989); maternally-derived genes are silenced to increase a child's resemblance to its father and thereby increase the amount of paternal care the child receives (Christenfeld and Hill, 1995); imprinting matches the size of a baby's head to the size of its mother's pelvis (Pembrey, 1996); inactivation of patrigenes in daughters and matrigenes in sons increases resemblance to samesex parents and enhances sex-specific fitness (Day and Bonduriansky, 2004); local adaptation is enhanced by matching offspring phenotype to the parent who disperses less (Spencer et al, 2004;Spencer and Clark, 2006). Wolf and Hager's (2006) model of 'maternal-offspring coadaptation' is often cited as the theoretical underpinning of the coadaptation hypothesis for the evolution of genomic imprinting.…”
Section: Phenotypic Matchingmentioning
confidence: 99%